Effects of exchange rate, output gap, and output gap volatility on inflation volatility in Turkey - Mustafa Özer; Zoran Grubišić; Sevilay Küçüksakarya (Journal of Central Banking Theory and Practice, 2023)
This study first investigates the short and long-run effectsof exchange rate, output gap and output gap volatility on inflationvolatility in Turkey by using the ARDL bounds testing approach.Second, we also examine the causal relationship among these vari-ables by using Toda-Yamamoto and frequency domain causalitytests developed by Breitung and Candelon. The results of the ARDLestimates indicate that the exchange rate, output gap and output gapvolatility have statistically significant effects on inflation volatility.Also, causality tests results indicate that changes in the exchangerate, output gap volatility, and output gap will have permanent andtemporary causal effects on inflation volatility. The policymakersshould carefully consider these results to implement appropriatepolicies to reduce inflation volatility. The finding that the shocks areof temporary nature will have particularly important implicationson the policies fighting against the inflation.This study contributes to the empirical inflation literature by iden-tifying both short run and long run effects of the exchange rate andoutput gap volatility and output gap together, as well as by providingevidence about the structure of the shocks created by these variableson inflation volatility. This study also identifies the sources of tem-porary and permanent shocks of inflation volatility.
Keywords: E31; F31; C22; 330; Inflation volatility; output gap/volatility; ARDL Boundstesting approach; Toda-Yamamoto causality test; Frequency DomainCausality Test